(untitled) (TAJ: Journal of Teachers Association, 2010)
Wilson’s disease (hepatolenticuler degeneration), an inborn error of copper metabolism, is an autosomal recessive disorder characterized by degenerative changes in brain, liver disease and Kayser Fleisher (KF) rings in the cornea. It is due to a defect of p-type ATPase which is probably required for normal excretion of copper through bile. Hepatic manifestation of the disease is common at early age and neurological manifestation is common at an older age. We are reporting Wilson disease with neurological manifestation in a 10 year old boy. TAJ 2010; 23(1): 87-90